PENGARUH ELEMEN-ELEMEN CRM TERHADAP CUSTOMER RETENTION YANG DIMEDIASI OLEH RELATIONSHIP QUALITY DAN CUSTOMER VALUE PADA UMKM BINAAN BOGASARI - Hendry Mangihut Tua (Jurnal Ekonomi Perusahaan, 2020)
Customer relationship management (CRM) is one of the strategies companies use to retain their customers. The elements in CRM can be applied to improve relationship quality and create customer value. The research method is quantitative with an explanatory research design. The study population is all UMKM fostered by Bogasari that use wheat flour as a base material in Jabodetabek. The sample in this study was 252 with a sampling technique based on purposive sampling. The analytical method uses structural equation modeling (SEM) with a Lisrel 8.80 program. The results showed that of the 10 research hypotheses there were 6 hypotheses that were accepted and there were 4 hypotheses that were rejected. Keywords: CRM; Relationship Quality; Customer Value; Customer Retention; SEM